Rare earth elements in middle precambrian volcanic rocks of Finland, with a discussion of the origin of the rocks - Koljonen, Tapio; Rosenberg, Rolf (Bulletin of the Geological Society of Finland, 1975)
The contents of rare earth elements (REE) have been determined in five Svecofennian metamorphosed volcanic rocks and are compared with those found in the Karelian zone and Recent tholeiites. In the Svecofennian zone, REE contents in low silica volcanic rocks are like those in the calc-alkalic series and in continental tholeiites, whereas in the Karelian zone they are like those in island arc tholeiites. It is argued that in the Karelian zone, where magmatism initiated, tholeiitic basalts originated in the upper mantle; as shown in normalized form, the light REE are depleted, reflecting the distribution pattern found, for example, in rocks of pyrrolite composition. As orogeny advanced, more and more crustal material — basement and geosynclinal sediments — was recycled and the REE distribution pattern changed to that found in the synorogenic calc — alkalic rocks (1.8—1.95 Ga), reflecting the REE pattern present in sediments. The chemical composition of the magmatic rock series formed during Sveco-karelian folding is quite like that observed in island arc systems.